Parcelamento de nitrogênio e potássio via fertirrigação no cultivo do abacaxizeiro - Ribeiro, Ana Maria Alves de Souza (2016)
The pineapple cultivation (Ananas comosus (L.) Merril) has increased in the state of Espírito Santo and has great potential to continue increasing, as it is well suited to the soil and weather conditions. Therefore, producers should adopt agricultural practices, including fertigation, which enhance the aspects of fruit quality, to maximize marketing. Due to the above, this study aimed to evaluate the productivity and fruit quality associated with the use of fertigation in São Mateus, northern Espírito Santo. The experiment was conducted at the Experimental Farm of the Federal University of Espírito Santo (UFES), located in São Mateus - Espírito Santo (ES). The experiment was designed in a randomized block design (DBC), with four replicates per treatment. Accordingly, we developed two studies: the first study, was concerning fertigation management alternatives: the control treatment was nonirrigated and non-fertirrigated parcels; irrigated treatment and non-fertirrigated; weekly fertigation with increasing doses, at a rate of 10% nitrogen (N) and potassium (K); fertigations held twice a week for nitrogen (N) and potassium (K) and treatment which was carried out 33% of nitrogen fertilization (N) and potassium (K) at the planting and the rest (67%) in weekly coverage fertigation. The second study, evaluated different nitrogen subdivisions (N) and potassium (K) by fertigation, comprised by: a control treatment (non-irrigated and non-fertigated); four subdivisions of topdressing nitrogen fertigation in a total of (4, 7, 27 and 54 applications); four subdivisions of topdressing potassium fertigation in a total of (4, 9, 35 and 70 applications) and an additional treatment (irrigated and non-fertirrigated). The variables were: fruit mass with crown (kg), productivity (kg ha-1), crown mass (g), crown length (cm), fruit length with crown (cm), uncrowned fruit length (cm), average fruit diameter (mm), firmness (N), pulp percentage (%), soluble solids (SS), pH, titratable acidity (AT) and relative (soluble solids/titratable acidity). Considering the variables evaluated, the use of fertigation, the treatment which applied 67% of N fertilizer and K weekly coverage, promoted the greatest length on uncrowned fruit. The treatments (non-irrigated and non-fertirrigated) and (irrigated and nonfertirrigated) resulted in higher values of soluble solids. The subdivisions of nitrogen fertilizers had no effect on fruit mass with crown and productivity, but the crown length and the fruit median diameter were significantly affected. The subdivisions of potassic fertilizers had significantly influence in the fruits mass with crown, productivity, average fruit diameter and pH.